Homens de caminho: trânsitos, comércio e cores nos sertões da América portuguesa - século XVIII - Isnara Pereira Ivo (2009)
This work aims to study the established relations between the captaincy of Minas Geraiss northern backwoods (Serro Frios county) and captaincy of Bahias backwoods, more specifically, the area known as Ressacas Backwoods. (Border with the North of the captaincy of Minas Gerais) and the High Backwoods of Bahia (Rio de Contas Village). The commercial relations during 18th century are learned as anexchanging exercise, in which the involved agents made the backwoods, the locus of cultural mediation that was integrated and it was defined in the context of expansion and advance toward the interior of Portuguese Empire. To comprehend this main question, the work was divided into four parts. First of all this work investigated the trajectory of three connectors agents of Portugals interests on the backwoods,illustrating how those mens actions were determinant to the economical and cultural connection of these areas to the overseas Portuguese world. The identification of the lands and water paths that conducted men, flavors, knowledge and experiences is also based on the explanation on how the Crown thought and administrated these places. Understood as a mixed space, the backwoods put together multiple tastes illustrated bythe consumption of its mixed population born from the gathering of people from different Origins.